Religious Intertextuality in the Narratives of Youssef Hadhai Mays: An Analytical Study - Make, Bassma Jabar (Thi Qar Arts Journal, 2025)
This research belongs to the field of narrative analysis through intertextuality, focusing on its function as a literary technique in the narrative style of Youssef Hadhai Mays, an Iraqi novelist from the southern region of Iraq. Mays has authored several novels that serve as the analytical foundation for this study, including Niran Wara, Asfad Min Waraq, Ya Ali, and the short story collection Mawsim Al-Qataf. His first literary work, Bayn Al-A’war wa Al-Shaytan, was published in 2010 by Yanabee Publishing House. His second novel, Asfad Min Waraq, was released in 2013 by Tamouz Publishing. In 2017, he published Niran Wara through Shahrazad Publishing, followed by Ya Ali in 2019 via Al-Warsha Al-Thaqafiya, and Magritte’s Apple in 2020 through Al-Nokhba Publishing. Mays is a member of the Iraqi Writers Union and has published numerous critical articles and impressionistic readings in both Iraqi and Arab newspapers and magazines. He has gained significant recognition for his literary and narrative contributions. The research consists of: • An introduction titled Key Concepts in the Study. • Chapter One: Narrative Intertextuality with the Holy Qur’an. • Chapter Two: Narrative Intertextuality with Hadith and the Sayings of Ahl al-Bayt. • Conclusion and References.